Gravestone in God's Acre at Bethabara Moravian Church, 1959. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 2-2-59 p.1.
Gravestone in God's Acre at Bethabara Moravian Church, 1959.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth